2016
DOI: 10.1097/aap.0000000000000184
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Neuraxial Ultrasound for Spinal and Epidural Anesthesia

Abstract: We know that neuraxial ultrasound is a useful complement to clinical examination when performing lumbar central neuraxial blocks. It provides anatomical information including the depth of the epidural space, the identity of a given intervertebral level, and the location of the midline and interspinous/interlaminar spaces. This information can be used to successfully guide subsequent needle insertion.Since 2010, new data from RCTs and 1 meta-analysis suggest that neuraxial ultrasound increases the success and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 265 publications
(98 citation statements)
references
References 47 publications
4
85
0
Order By: Relevance
“…Specific methodologies for the various components of this project are detailed in the accompanying individual articles. [2][3][4][5][6][7][8][9] In brief, putative evidence was gathered using a variety of standard electronic search engines to identify relevant literature, concentrating on the period from 2009 through spring 2015. The specific search engines used, language limitations, and MeSH (medical subject headings) are described in the individual articles.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific methodologies for the various components of this project are detailed in the accompanying individual articles. [2][3][4][5][6][7][8][9] In brief, putative evidence was gathered using a variety of standard electronic search engines to identify relevant literature, concentrating on the period from 2009 through spring 2015. The specific search engines used, language limitations, and MeSH (medical subject headings) are described in the individual articles.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, several meta-analyses that include safety issues have been published. 6,12,16 Safety issues related to neuraxial anesthesia were addressed previously in that section.…”
Section: Patient Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis concluded that neuraxial ultrasound more accurately identifies the lumbar intervertebral space over palpation, accurately predicts the distance from the skin to the epidural space, and improves efficacy. 57 However, with some practitioners, the actual depth from the skin to the intended space may differ by as much as 15 mm from that estimated by ultrasound. 7-9,21 Significant training and experience is necessary before one can properly utilize ultrasound for assistance with epidural needle and catheter placement.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple recently published systematic reviews found ultrasound guidance to improve the performance of the blocks and different patient outcomes [11][12][13][14]. Importantly, the expectation that direct visualization of the neural structures would reduce the incidence of neurologic complications has not been confirmed, but ultrasound guidance has been found to reduce the risk of local anesthetic systemic toxicity and possibly pneumothorax [15 & ].…”
Section: Alternatives To Neuraxial Analgesiamentioning
confidence: 99%